ANALISIS KEBERHASILAN KOPERASI AMANAH KECAMATAN LANGKAPURA KOTA BANDAR LAMPUNG - Haliana Ghaida Sanjaya; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Lampung University, 2017)
This research aims to determine the business entities performance of Amanah Cooperative, contribution of the cooperative toward development, and the satisfaction level of members to service performance at the cooperative. This research was conducted at Amanah Cooperative in Langkapura subdistrict of Bandar Lampung City. Respondents were 68 active members of Amanah Cooperative. Data were analyzed by using descriptive analysis, service quality (servqual), and importance performance analysis (IPA). The results showed that Amanah Cooperative performance was included in medium category. Contributions of Amanah Cooperative development were seen from (a) obedience of the cooperative in tax payment which is zero because the cooperative suffered losses, (b) employment growth which was not yet known, because this year was the first year of cooperative activity, (c) the wage level of employees which was not good because it was less than regional minimum wage. The members were not satisfied by services especially on the dimensions of responsiveness. Attributes considered to be important were supporting facilities of the work space, supporting physical infrastructure for the reception area, counter staff, administrative employee rooms, completion service process of members from the beginning to the end, availability of brochures or bulletin boards, the service officer information, and the accuracy of the information provided. Key words: cooperative, performance, success